Improved heat-insulating products for ingot hot-tops in molds without extensions - Akreiev , V.V.; Cherenkov , D.V.; Prykhodko , S.V.; Melnyk , S.O.; Ovcharuk , A.M. (Theory and Practice of Metallurgy, 2025)
The fundamental principle of proper ingot solidification in metal molds - hop top part of ingot should cool and solidify slowly than the ingot body. To achieve this, typically hop top parts of ingots are insulated with special thermal insulation products. They are mounted either directly on the inner surface of the mold or installed in special hop top extensions of the mold. This approach effectively directs shrinkage defects away from the usable ingot section into hop top cut zone. For different steel grades (alloys), depending of the application, ingot design, and casting method, hop top cut ranges from 8% to 16% of the total ingot mass. This article presents experience in using an advanced thermal insulation insert design, which enables higher part of usable ingot metal, prevents subhead cracks in the ingot, simplify and lighten the lining of ingot hop top.